The Determinants Of Firm Performance Of Indonesian Listed Companies - Kaylsi, Helmi Khairunnisa Putri; Khoiruddin, Moh. (Management Analysis Journal, 2021)
One of the important aspects in the company is company performance. In company performance, there are aspects of financial performance that are important to measure in order to get a picture of the company’s financial condition. This study aims to examine the effect of firm size, growth opportunity, and asset structure on financial performance with capital structure as an intervening variable. This research is a quantitative research. The samples of this study are property and real estate companies listed on the IDX for the 2015-2019 period. The data collection method uses the documentation method from secondary data in the form of an annual report that has been published on the IDX. The data analysis method used is multiple regression method and single test. Firm size, growth opportunity, asset structure and capital structure have a 74. 51% influence on the performance of property and real estate companies. This study shows that firm size, asset structure and capital structure have a negative effect on firm performance, while growth opportunity has no effect on financial performance. The capital structure has not been able to mediate the effect of independent variables on financial performance.